Mass distribution of azithromycin and child mortality among underweight infants in rural Niger: a subgroup analysis of the AVENIR cluster-randomised trial - Catherine E Oldenburg; Thomas M Lietman; Elodie Lebas; Amza Abdou; Travis C Porco; Ramatou Maliki; Benjamin Arnold; Brittany Peterson; Ahmed Arzika; Bawa Aichatou; Ismael M Bello; Diallo Beidi; et al. (BMJ Open)
Objective Azithromycin has been shown to reduce all-cause child mortality. This subgroup analysis investigates azithromycin’s mortality impact by underweight status using Azithromycine pour la Vie des Enfants au Niger: Implementation et Recherche (AVENIR) trial data.Design The AVENIR trial randomised communities into three arms: azithromycin for children aged 1–59 months, azithromycin for infants aged 1–11 months or placebo. Weight-for-age z-score was used to categorise children into subgroups of either moderate to severe underweight or not and severe underweight or not.Setting 2880 communities with a population of less than 2500 people in the Dosso and Tahoua regions of Niger that participated in the AVENIR trial were included.Participants 97 572 children aged 1–59 months who had weight captured during at least one census participated.Results Underweight subgroups had higher overall mortality compared with non-underweight subgroups. IRDs of deaths in children aged 1–11 months comparing communities receiving azithromycin to children 1–59 months of age to placebo were −6.2 deaths per 1000 person-years (95% CI −9.3 to −2.6) overall, −8.0 (95% CI −15.9 to −0.4) in the moderate to severe subgroup and −11.2 (95% CI −26.0 to −2.1) in the severe subgroup. Similar trends were noted in the azithromycin 1–11 month comparison. Malnutrition was not a statistically significant effect modifier for either comparison.Conclusions Although analyses suggest the potential for stronger effects in more severe underweight subgroups, we were unable to demonstrate underweight status as an effect modifier. In fact, azithromycin mass drug administration to children 1–59 months old reduced mortality in all subgroups, and, especially as the number of lives saved would be the highest by treating all subgroups, our results do not support restricting eligibility for this intervention.Trial registration number clinicaltrials.gov NCT04224987.